The Effect Of Innovation Orientation On Supply Chain Disruption Recovery, The Mediating Role Of Supply Chain Robustness - Akagwire, Vincent Atoli-igne (KNUST, 2023)
A thesis submitted to the institute of distance learning, kwame nkrumah university of science and technology, kumasi, in partial fulfillment of the requirements for the award of the degree of master of science in logistics and supply chain management.